An Updated Evaluation of the Management of Nerve Gaps: Autografts, Allografts, and Nerve Transfers - Johnson, Anna Rose; Said, Abdullah; Acevedo, Jesus; Taylor, Ruby; Wu, Kitty; Ray, Wilson Z.; Patterson, J. Megan; Mackinnon, Susan E. (Seminars in Neurology, 2024)
Within the past decade, there have been multiple innovations in the field of nerve surgery. In this review, we highlight critical changes and innovations that have helped advance the field and present opportunities for further study. This includes the modification and clarification of the classification schema for nerve injuries which informs prognosis and treatment, and a refined understanding and application of electrodiagnostic studies to guide patient selection. We provide indications for operative intervention based on this nerve injury classification and propose strategies best contoured for varying injury presentations at differing time points. Lastly, we discuss new developments in surgical techniques and approaches based on these advancements.
Keywords: nerve repair; nerve autograft; acellular nerve allografts; nerve transfers